Vestibular test and electronystagmography in the diagnosis of vertigo - ., Zorengpuii; P., Naveen (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Vertigo, by definition, is a subjective sense of imbalance, and can result from a variety of disorders both peripheral and central. Although perfect function is required for precise balance and eye movement control, man is able to function adequately with only two of the three main sensory inputs. Great difficulty, however, occurs if only one system is intact, or if the control integrating mechanisms within the nervous system are deranged. Minor deficiencies of any, or all three sensory inputs may give rise to symptoms of imbalance. The disorders causing vertigo may be of peripheral or central origin, and accurate diagnosis of the underlying pathology is warranted for effective treatment. Methods: The study was carried out in the Department of Otorhinolaryngology, Regional Institute of Medical Sciences, Imphal. 50 cases presenting with symptoms of vertigo were studied irrespective of age, sex, caste, religion, socio-economic status and duration of illness. They were subjected to a thorough clinical examination and relevant investigations with main emphasis on vestibular tests and electronystagmography in every patient. Results: Vertigo of peripheral and central lesions accounted for 64% and 12% respectively. Idiopathic vertigo in which no neurotological abnormality is detected accounted for 24% of cases. Meniere’s disease (28%) comprised the single largest group amongst the peripheral vertigo. Majority of the patients (58%) presented with hearing impairment as associated symptom. Conclusions: Ninety percent of patients presented with less than one year duration of vertigo. Vertigo caused by peripheral vestibular lesion presents as acute, unprecipitated, short-lived episodes associated with nausea and vomiting, while vertigo of central vestibular origin follows a more gradual and insidious onset of continual imbalance.